1999
DOI: 10.1002/(sici)1522-2675(19990707)82:7<1096::aid-hlca1096>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Hydrosilylation of Ketones with Rhodium-Phosphite Complexes Containing a TADDOLate and a Dihydrooxazole Unit

Abstract: New types of chiral phosphorus/nitrogen ligands, capable of forming six‐membered‐ring metal chelates have been prepared from α,α,α′,α′‐tetraaryl‐1,2‐dioxolane‐4,5‐dimethanols (TADDOLs), PCl3, and dihydrooxazole alcohols (from amino acids) (7 in Scheme 1). The X‐ray crystal structure of a Rh complex of one of these ligands, 8b, has been determined (Scheme 2 and Fig.). Enantioselective hydrosilylations of dialkyl and aryl alkyl ketones with Ph2SiH2/0.01 equiv. RhI⋅7 have been studied and found to provide seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…Furthermore, there is considerable current interest in hybrid P/N ligands and a search in the Cambridge Structure Database revealed that although a vast number of Groups 9-10 complexes with nitrogen and phosphorus ligands have been characterised structurally, only a relatively small number of Pd(II) cations and Rh(I) cations [54][55][56][57][58][59][60][61][62][63][64][65] containing bidentate N(sp 2 )-P(sp 3 ) donors are reported. Since bulky substituents at the aryl groups of N(sp 2 ) donors have been found to strongly influence the catalytic activity and selectivity of Group 10 complexes [66], it is surprising that no Rh(I) complexes of ligands combining tertiary phosphine donors and (sp 2 )N-aryl donors with bulky ortho substituents have been structurally investigated.…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, there is considerable current interest in hybrid P/N ligands and a search in the Cambridge Structure Database revealed that although a vast number of Groups 9-10 complexes with nitrogen and phosphorus ligands have been characterised structurally, only a relatively small number of Pd(II) cations and Rh(I) cations [54][55][56][57][58][59][60][61][62][63][64][65] containing bidentate N(sp 2 )-P(sp 3 ) donors are reported. Since bulky substituents at the aryl groups of N(sp 2 ) donors have been found to strongly influence the catalytic activity and selectivity of Group 10 complexes [66], it is surprising that no Rh(I) complexes of ligands combining tertiary phosphine donors and (sp 2 )N-aryl donors with bulky ortho substituents have been structurally investigated.…”
Section: Introductionmentioning
confidence: 63%
“…Observed pK a values range from approximately 35 (for NHalkyl), through 28 (for NHaryl), 17 (for OH and NHCOR), and 10 (for SH, NHCOCF 3 , or NHR 2 ), down to as low as 6 (for NHSO 2 CF 3 ). [90] After many attempts [91,92] we finally succeeded [76] in introducing PR 2 groups directly at the diarylmethyl carbon atom (although preparation of a tetraphenyl DIOP derivative [93] has still not been accomplished).…”
Section: Preparation Of Taddols and Their Analoguesmentioning
confidence: 99%
“…The results of using the rest of the phosphite-oxazoline ligands (1)(2)(3)(4)(5)(6)(7)(8) under the optimized conditions are showed in Table 2.…”
Section: Asymmetric Hydrosilylation Of Ketonesmentioning
confidence: 99%
“…Mixed N-N [2a,b,e,g] and P-N[2h,j-l,q,r] ligands have played a dominant role among the heterodonor ligands [1]. Regarding P-N heterodonor ligands, the phosphite-oxazoline combination have been less studied despite the early success of the TADDOLbased phosphite-oxazoline ligands developed by Heldmann and Seebach for this process [3]. More research is therefore needed to study the possibility offered by the phosphite-oxazoline as a new type of ligands for this process.…”
Section: Introductionmentioning
confidence: 99%